Characterization of bioethical aspects of complaints to the Health Authority in Chile in the odontological area - Portela León, Francisco José (Acta Bioethica, 2013)
This investigation identifies common denominators of complaints presented to Health Superintendent in the form devoted to mediation related to private providers, evincing the breakdown of the odontologist-patient relationship and in addition analyzes the contents of narratives expressing dissatisfaction with unfulfilled expectations, emphasizing its ethical component. There is a qualitative analysis of narratives included in the forms using content analytic techniques and a quantitative analysis providing data on odontological specialties involved and sociodemographic data. Part of the dissatisfaction is related to bad ethical handling on the part of the professionals, deteriorating the personal relationship. Complaints could be reduced by the inclusion of ethical norms in the interpersonal relation, pointing towards recognition of the other, his/her dignity and the improvement of ethical consciousness as professionals.